Making the moose out of life - Oldland, Nicholas (Kids Can Press, 2010)
Although he lives in the wild, this timid, wide-eyed moose is anything but. While his friends go puddle jumping in the rain, he cowers under an umbrella, and he looks on shivering when others go skiing: "Not this moose. Too cold." Sensing he's "missing out on something," the moose decides to "take life by the antlers" and sets sail in a boat that breaks apart in a storm. Stranded on a remote island, he not only summons survival skills-foraging for food, building shelter and a fire, but happily swims and surfs with a new tortoise pal.